Implementasi Model Contextual Teaching and Learning Berbantuan Media Pembelajaran Flipbook Digital untuk Meningkatkan Penguasaan Materi Getaran dan Gelombang Peserta Didik Kelas VIII - Telinila Rumahenga; Cicylia T. Kereh; Herman S. Wattimena (Polygon : Jurnal Ilmu Komputer dan Ilmu Pengetahuan Alam, 2025)
Conventional physics learning tends not to connect the material studied by students with their environment. Learning needs to be designed contextually by teachers using the Contextual Teaching and Learning model. The use of digital Flipbook media is intended to be accessible to the students anytime and anywhere. This research aims to determine the increase in mastery of vibration and wave material in class VIII2 students at SMPN 8 Ambon. This type of research is one group pretest-posttest, with 28 students as research samples obtained by using purposive sampling techniques. This research data was collected through test and non-test instruments. Test instrument was used for initial tests and final tests, while non-test instruments are Student Worksheets (LKPD) and student response questionnaires. The results of the research showed that 100% of the students' initial abilities were in the failing qualification with an average score of 23.0. During the learning process, the average student achievement score was 82.6 or good qualifications. The average final test achievement score of students reached 82.4 with good qualifications. For the N-Gain Test results, the average student score was 0.77 or high qualification. Students' responses to digital flipbook media in learning science (physics) achieved very good qualifications with an average score of 98.47. Thus, it can be concluded that the application of the Contextual Teaching and Learning model assisted by digital Flipbook media can improve the mastery of vibration and wave material for class VIII2 students at SMPN 8 Ambon.